Report of the Study Team on Tribal Development Programmes Himachal Pradesh - Planning Commission, Government of India (Planning Commission, Government of India, 1977)
The Study Team Report on Tribal Development Programmes in Himachal Pradesh evaluates the socio-economic conditions of the state’s tribal populations and proposes targeted interventions for their welfare. With tribal communities concentrated in Kinnaur, Chamba, and Lahaul & Spiti, the report identifies disparities among tribes such as Gaddis, Gujjars, and Kinnauras. Key recommendations include conducting detailed socio-economic surveys, revitalizing advisory structures, improving agriculture and irrigation facilities, establishing educational institutions with boarding facilities, providing mobile medical services, enhancing infrastructure in remote regions, and promoting cooperatives and local industries. The report presents a comprehensive strategy to foster inclusive, sustainable development, empowering tribal communities through improved access to resources, education, healthcare, and economic opportunities.
Committee on Plan Projects Planning Commission
Committee on Plan Projects Planning Commission
Keywords: Tribal Development; Himachal Pradesh; Kinnaur; Lahaul & Spiti; Gaddis; Gujjars; Kinnauras; Socio-Economic Surveys; Agriculture; Irrigation; Education; Healthcare; Infrastructure; Cooperatives; Inclusive Development